Apert Syndrome: Case Series and Review of The Literature - Silvina, Silvina; Khairiza, Rizka; Setyarto, Muhammad Rizqy (Lingkar Studi Bedah Plastik Foundation, 2021)
Summary: Apert syndrome is a type 1 acrocephalosyndactyly, a rare syndrome characterized by the presence of multiple craniosynostoses, dysmorphic facial manifestations, and syndactyly of hand and feet. It affects 1:100.00 of birth and the second most common of syndromic craniosynostosis. Molecular genetic tests that identify the heterozygous pathogenic variant in FGFR2 genes - identical with Apert syndrome cost too high to be applicable in developing countries. Therefore, the diagnosis of Apert syndrome should be suspected from the clinical findings. Three cases from the Community of Indonesian Apert Warrior Group were collected. These series were based on medical and surgical records. We obtained the patient characteristic from the phenotypic manifestations only. We present cases of 6-years-old male, 2-years-old female, and 3-years-old female, respectively, with similar anatomical findings, such as skull shape abnormality, midface hypoplasia, intraoral disfigurement, and hands and feet deformities that resemble Apert Syndrome. Our series presents similar Apert syndrome characteristics, such as typical craniofacial dysmorphic with symmetrical syndactyly of both upper and lower extremities. These clinical findings are essential to establish an initial diagnostic of Apert Syndrome.